Strength and ductility of high-strength concrete cylinders externally confined with steel strapping tensioning technique (SSTT) - Lee, Hoong-Pin (Penerbit UTM Press, 2014)
This research study is to introduce and investigate an effective technique of external pre-tensioning using steel strapping (SSTT) to reduce the brittleness and enhance the ductility of high-strength concrete cylinders. Fifteen cylinders with dimension of 150 mm and 300 mm in diameter and height respectively were casted, pre-tensioned with two and four layers of steel strapping and tested to failure under uniaxial monotonic and cyclic compression. The behaviour of SSTT confined cylinders was studied through their stress-strain relationship upon the longitudinal deflection, transverse strain, mode of failure, confinement ratio, and existence of an envelope curve. It is experimentally proved that SSTT confinement do helps in controlling the brittleness problem of high-strength concrete and at the same time, enhancing both the concrete ductility and compressive strength up to 46.2 % and 112.5 % respectively. The envelope curve of uniaxial cyclic loading also coincides with the corresponding monotonic loading curve, regardless of any loading activity. The observed stress-strain relationship of confined cylinders with different confining ratios are compared with existing strength and strain models and a stress-strain prediction model, the result showed a linear relationship between the compressive strength and strain enhancement and confining ratio, with acceptable agreement between the prediction model.